Asymmetric synthesis of spirooxindole–pyranoindole products via Friedel–Crafts alkylation/cyclization of the indole carbocyclic ring. (2nd June 2020) - Gao, Yuan; Wang, Xiaonan; Wei, Zhonglin; Cao, Jungang; Liang, Dapeng; Lin, Yingjie; Duan, Haifeng
Abstract : Enantioselective Friedel–Crafts alkylation/cyclization of the indole carbocyclic ring with isatylidene malononitriles was performed using a new bifunctional catalyst. Abstract : An efficient enantioselective Friedel–Crafts alkylation/cyclization tandem reaction of the indole carbocyclic ring with isatylidene malononitriles has been performed successfully by using a new bifunctional tertiary amine-urea catalyst. A series of chiral spirooxindole–pyranoindole products were obtained in excellent yields (up to 98% yield) with moderate to good enantioselectivities (up to 85% ee).